CFD Modeling and Experimental Validation of a Solar Still - Mahmood, T. (EDP Sciences, 2017)
Earth is the densest planet of the solar system with total area of 510.072 million square Km. Over 71.68 of this area is covered with water leaving a scant area of 28.32 for human to inhabit. The fresh water accounts for only 2.5 of the total volume and the rest is the brackish water. Presently, the world is facing chief problem of lack of potable water. This issue can be addressed by converting brackish water into potable through a solar distillation process and solar still is specially assigned for this purpose. Efficiency of a solar still explicitly depends on its design parameters, such as wall material, chamber depth, width and slope of the zcondensing surface. This study was aimed at investigating the solar still parameters using CFD modeling and experimental validation. The simulation data of ANSYS-FLUENT was compared with actual experimental data. A close agreement among the simulated and experimental results was seen in the presented work. It reveals that ANSYS-FLUENT is a potent tool to analyse the efficiency of the new designs of the solar distillation systems. © The authors, published by EDP Sciences, 2017.